Concomitant Sacral Neuromodulation and Gynecologic Surgery: A Single‐Institution Experience. Issue 8 (15th December 2019) - Sudol, Neha T.; Brueseke, Taylor J.; Lo, Alyssa; Noblett, Karen L.
Abstract : Aims: Sacral Neuromodulation (SNM) is a safe and minimally invasive treatment for urinary and fecal pelvic floor disorders (PFDs). With a high prevalence of women reporting multiple PFDs, knowledge regarding concomitant surgery may inform optimal patient care. Our literature search did not identify any published data on this topic, thus we sought to report our experience with concomitant SNM and gynecologic surgery. Our primary objective was to identify the rate of adverse events among cases. Secondarily, we reviewed the anesthetics used to identify potential associations when performing combined surgery. Materials and Methods: This was retrospective case series of women undergoing SNM at a single academic center from 2012 to 2018. Cases were identified using current procedural terminology codes for SNM and common gynecologic procedures. These electronic medical records were reviewed to identify cases that occurred concomitantly in addition to obtaining demographics, adverse events, type of anesthesia, and overnight hospital stay. Descriptive data analysis was performed with Excel. Results: Of 200 identified cases of SNM, 15 (7.5%) were concomitantly performed with another procedure. Most concomitant surgeries occurred with insertion of implantable pulse generator. Three minor adverse events occurred: two urinary tract infections and one occurrence of urinary retention. Eight (53%) cases were performed under general anesthesia while seven (46%) received monitored sedation. Conclusions: No serious adverse events or anesthesia‐related complications were identified in this series. While general anesthesia was used more often, it was in accordance with our standard practice for the gynecologic procedures. This study supports the safety of concomitant gynecologic and SNM surgery.